2020
DOI: 10.3390/f11060619
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Small-Scale Forestry and Its Influencing Factors in Lithuania

Abstract: Small-scale private forestry is widespread in many countries and occupies 40.3% of the total forest area in Lithuania. The pursuit of sustainability has become one of the main goals of forest policy. In order for small-scale private forestry to be based upon sustainability principles, its sustainability must first be assessed and analyzed. This study assesses the sustainability of 385 small forest holdings of Lithuania using established forest sustainability assessment methods and performs an analysis of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The structural characteristics of the forests, with the predominant age class of the stands in the forest holding (MATURITY) on the one hand, and the predominant forest type (COMPOSITION) on the other hand, influence and are influenced by forest management activities [40,93]. Juutinen et al [35] and Eggers et al [38] point out that forest-related factors, such as age-class distribution, are important variables for analyzing the management decisions of small owners, and their omission may limit the results and the conclusions derived from these.…”
Section: Factors Influencing the Willingness To Engage In Forest Mana...mentioning
confidence: 99%
See 1 more Smart Citation
“…The structural characteristics of the forests, with the predominant age class of the stands in the forest holding (MATURITY) on the one hand, and the predominant forest type (COMPOSITION) on the other hand, influence and are influenced by forest management activities [40,93]. Juutinen et al [35] and Eggers et al [38] point out that forest-related factors, such as age-class distribution, are important variables for analyzing the management decisions of small owners, and their omission may limit the results and the conclusions derived from these.…”
Section: Factors Influencing the Willingness To Engage In Forest Mana...mentioning
confidence: 99%
“…It can be seen that many studies primarily identify socio-demographic and socio-economic variables (e.g., age, gender, educational level, place of residence) as influencing factors for forest management activities [27][28][29][30][31][32][33][34][35][36][37]. Furthermore, characteristics of forest ownership (e.g., size of ownership, distance from home, income from forestry, membership in a forest owner association) have been found to influence forest management [27,29,33,34,[38][39][40]. However, the factors so far identified as influencing the activities of forest owners are apparently only partially sufficient to develop appropriate instruments for small owners.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the research conducted by Mizaras et al confirmed that achievement of sustainability is one of the main objectives of forest policy. The scientists noted that rational management of small-scale private forestry should be based on the principles of sustainability [34]. For the implementation of this purpose, it is necessary to establish a social and economic database of private forest owners in Lithuania.…”
Section: The Concept Of Socio-economic and Legal Data Of Private Fore...mentioning
confidence: 99%
“…The State Forestry Service provides these statistical data every year, but socio-economic data are still missing. In the Republic of Lithuania, regarding the attitude of private forest owners to managing property, their values and farming goals, etc., no monitoring system has been created, and only isolated and inconsistent investigations have been carried out [2,14,16,[34][35][36]. The results of the research conducted by Mizaras et al confirm that achievement of sustainability is one of the main objectives of forest policy.…”
Section: Data Submissionmentioning
confidence: 99%